Incidence and antimicrobial resistance of enteropathogens isolated from an integrated aquaculture system - Ribeiro, R.V; Reis, E.M.F; Reis, C.M.F; Freitas‐Almeida, A.C; Rodrigues, D.P (Letters in applied microbiology, 2010)
Aims: To evaluate an integrated aquaculture system, microbiological analyses of water used in this system were carried out and the incidence and antimicrobial resistance of enteropathogens were determined in the related ecosystem. Methods and Results: Microbiological analysis was undertaken for Salmonella sp., Shigella sp., Vibrio sp. and Aeromonas sp. The disc‐diffusion method was performed according to the Clinical and Laboratory Standards Institute. Water samples tested had 32·9% of faecal coliform rates (≤1600 per 100 ml) in accordance with WHO for pisciculture in wastewater. Salmonella spp. were detected in 14·5% of the samples. From a total of 33 strains, 15·1% were resistant to one or two antimicrobial drugs tested and multidrug resistance was not observed. Aeromonas spp. were identified in 91·6% of the samples. From a total of 416 strains, resistance to one antimicrobial class was observed in 66·3% and multidrug resistance in 37·7%. Conclusions: This system reflects the community profile, drawing attention to the circulation of pathogens, because the genes coding for resistance to classical antibiotics and broad spectrum are a public health problem. Significance and Impact of the Study: The reuse of water resources requires continuous monitoring as the system is subject to treatment failure, which can result in the spread of bacterial pathogens.